Abstract Volume of Sixth Nepal Geolgical Congress on Geology, Natural Resources, Infrastructures, Climate Change and Natural Disasters, 15 – 17 November 2010, Kathmandu, Nepal - Rai, Santa Man (Journal of Nepal Geological Society, 2012)
This is the full volume of the Abstracts from the Sixth Nepal Geolgical Congress on Geology, Natural Resources, Infrastructures, Climate Change and Natural Disasters, 15 – 17 November 2010, Kathmandu, Nepal Journal of Nepal Geological Society, 2010, Vol. 41 (Sp. Issue)